Internet as a source of information in public health. Part III. The role of information in public health and threats linked to obtaining public health information on the Internet - Bryła, Marek; Stegienta, Grzegorz; Kowalska, Alina; Maniecka-Bryła, Irena (Polish Journal of Public Health, 2009)
The paper departs from information needs in public health. These are needs of all users of information in the field of health policy, depending on their interest profile. Taking into account such a viewpoint, we distinguished the following categories of the Internet users: students of medical faculties and related faculties, academics, active doctors, administrators and managers of various public and private institutions which operate in the sphere of health as well as decision-makers creating health laws, i.e. all those who participate in building the domain of public health. We devote a lot of space to the analysis of potential threats, which may appear in the process of searching for public health information in the global network like the Internet. We distinguish three principal types of threats: 1) related to the information quality (the possibility of getting information being irrelevant, wrong outdated, useless or of little value), 2) related to the legality of obtained information (e.g. a book copyright may prevent its dissemination, and still this publication is available on a website), and 3) technical threats (the possibility of capturing confidential data by third parties while sending or receiving). It ought to be emphasised that there are ways to minimise these threats. We quote the example of the Health on the Net Foundation, which worked out a code of several criteria, which, if fulfilled, enable to award certificate to www pages presenting information on human health.